Business Leadership in the Chinese Context: Trends, Findings, and Implications. (July 2014) - Zhang, Zhi-Xue; Chen, (George) Zhen Xiong; Chen, Ya-Ru; Ang, Soon
Abstract: Business leaders constitute a powerful driving force for the miraculous growth of the Chinese economy in the past few decades. However, scholars have not developed theories accounting for the unique leadership phenomenon in the Chinese context, characterized by high uncertainty, intense market competition, and constant changes in government regulations and policies. This special issue aims at offering insights regarding business leadership in China. In this paper, we first introduce the three streams of Chinese leadership research, varying in the degree of Chinese context being considered in theory development. We then discuss how Chinese leadership has co-evolved with the transformation of firms and the institutional environment in China. The new values of young employees, born after 1980, are driving the need for leaders to adjust their leadership practices once again. After that, we present a summary of the four papers in this special issue, and the insights they provide to our understanding of leadership and its effectiveness in the Chinese context. Finally, we suggest future research directions for Chinese leadership research.